Housing, Mobility and Unemployment - Thomas J. Dohmen (Institute for the Study of Labor (IZA), 2000)
This paper develops a model that shows why high-skilled workers move more and are therefore unemployed less than low-skilled workers. The model can explain the paradoxical empirical regularity that higher owner-occupation rates are associated with higher levels of unemployment although home-owners tend to be unemployed less. The choice of housing tenure affects moving costs and thereby regional mobility and unemployment. The paper analyzes the impact of symmetric and asymmetric shocks on mobility and unemployment, and discusses effects of government intervention in the housing market. In addition, it is shown that moving costs reduce job search effort and search effectiveness.
Keywords: J6; 330; Housing; mobility; unemployment; Regionale Arbeitsmobilität; Regionale Arbeitslosigkeit; Theorie der Arbeitslosigkeit; Tenure choice; Wohneigentum; Arbeitsuche; Wohnungswechsel; Kosten; Theorie